PENERAPAN TEKNOLOGI TEPAT GUNA MELALUI PEMBUATAN WEBSITE UMKM DAN ALAT PENABUR BENIH-PUPUK UNTUK MENDUKUNG PEREKONOMIAN DAN PERTANIAN - Afriani, Raden Irna; Ryzkiansyah, Ryan; Jannah, Mariyatul; Ramadiansyah, Dony; Rustandi, Tata; Ramadhan, Akkas; Nugraha, Bagas Muda (Yayasan Education and Social Center, 2025)
This appropriate technology implementation program was carried out by a community service team from Universitas Bina Bangsa in Mekarsari Village, Pulomerak District, Cilegon City, focusing on the economic and agricultural sectors. The program aimed to address the challenges faced by UMKM (Micro, Small, and Medium Enterprises) Masaru Berkah Medaksa in marketing its passion fruit herbal products, as well as the Kelompok Wanita Tani (KWT) farmers group that still relied on traditional planting methods. The solutions provided included the development of a website as a digital marketing platform and the design of a seed-fertilizer spreader to improve agricultural efficiency. The implementation method consisted of observation, interviews, design, implementation, training, and participatory evaluation. The results showed that the website successfully enhanced the professional image and market reach of the UMKM, while the seed-fertilizer spreader accelerated the planting process, reduced farmer fatigue, and produced more uniform seed distribution. This program not only delivered direct benefits in improving the local economy and agricultural efficiency but also fostered community awareness of the importance of sustainable use of simple, locally-based technologies.